Lithospheric flexure due to prograding sediment loads: implications for the origin of offlap/onlap patterns in sedimentary basins - Watts, A (1989)
Simple elastic plate models have been used to determine the stratigraphic patterns that result from prograding sediment loads. The predicted patterns, which include coastal offlap/onlap and downlap in a basinward direction, are generally similar to observations of stratal geometry from Cenozoic sequences of the US Atlantic and Gulf Coast margins. Coastal offlap is a feature of all models in which the water depth and elastic thickness of the lithosphere, Te, are held constant, and is caused by a seaward shift in the sediment load and its compensation as progradation proceeds. The stratal geometry that results is complex and depends on the sediment supply, the amount of subsidence, and Te. Lithospheric flexure due to prograding sediment loads is capable of producing a wide variety of stratal geometries and may therefore be an important factor to take into account when evaluating the relative role of tectonics and eustatic sea-level changes in controlling the stratigraphic record. -from Author